Quo Vadis: Sanctions for Children Facing the Law - Balla, Herman; Asriyani, Arini (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2021)
The study aims to find out the setting for the sentencing of sanctions against children who commit criminal acts of abuse resulting in death. The type of research used by the author is the empirical normative research type. The results showed that the regulation of sanctions against children who commit crimes that are sentenced to criminal sanctions has been contained in Article 71 paragraph (1) to paragraph (5) of Law No. 11 of 2012 concerning the Criminal Justice System of Children. In addition to the type of sanctions contained in Article 71, sanctions actions can also be imposed on children who commit criminal acts and the overall number of cases obtained from the results of research in the Sungguminasa Court is a total of 7 cases and in its ruling the tendency of judges to give criminal sanctions to prison for children perpetrators of crimes that result in death.